2018
DOI: 10.1371/journal.pone.0191871
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic alterations in the nymphal instars of Diaphorina citri induced by Candidatus Liberibacter asiaticus, the putative pathogen of huanglongbing

Abstract: Currently, huanglongbing is the most damaging disease of citrus causing huge economic losses. The disease is caused by the Gram-negative bacterium Candidatus Liberibacter asiaticus (CLas). The pathogen is transmitted in a persistent propagative circulative manner within its vector, the Asian citrus psyllid, Diaphorina citri. Exploring the metabolic alteration in the vector may lead to a better understanding of the nutritional needs of CLas and to designing an artificial medium for culturing the pathogen. It ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
(87 reference statements)
2
11
0
Order By: Relevance
“…The enzymes that catalyze the first and the second step in fatty acid β-oxidation and the production of acetyl-CoA, as well as enzymes involved in the citric acid cycle, were induced in Las-positive D. citri adult. Citric acid was induced in both Las-positive D. citri nymphs and adults Killiny and Jones 2018). Succinate dehydrogenase and succinate semialdehyde dehydrogenase enzymes were also enhanced in Las-positive D. citri ).…”
Section: Immune System and Metabolismmentioning
confidence: 92%
See 3 more Smart Citations
“…The enzymes that catalyze the first and the second step in fatty acid β-oxidation and the production of acetyl-CoA, as well as enzymes involved in the citric acid cycle, were induced in Las-positive D. citri adult. Citric acid was induced in both Las-positive D. citri nymphs and adults Killiny and Jones 2018). Succinate dehydrogenase and succinate semialdehyde dehydrogenase enzymes were also enhanced in Las-positive D. citri ).…”
Section: Immune System and Metabolismmentioning
confidence: 92%
“…Las-positive D. citri adults have less hexamerin, an amino acid-storage protein, which suggests that Las may manipulate free amino acid viability (Kruse et al 2017). Moreover, the concentrations of L-proline, the main energy source of insects (Teulier et al 2016), and L-aspartic acid were lower in Las-positive D. citri compared with the uninfected control Killiny and Jones 2018). The decrease in both amino acid concentrations may result from their oxidation to supplement the TCA cycle intermediates, which have higher demand under the energetic stress caused by Las infection.…”
Section: Immune System and Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…The full list of expressed genes, names, accession numbers, and primers are available in Table S2 and uninfected D. citri adults; 56 however, it was detected as a trace in D. citri nymphs reared on healthy or CLas-infected Valencia sweet orange flushes without any significant differences between them. 66 Another probability for the reduction of melatonin is due to the downregulation of the enzymes involved in melatonin biosynthesis. Our gene expression results showed that the expression levels of all enzymes involved in melatonin biosynthesis were decreased in CLas-infected D. citri, including DcTPH-1, DcTPH-2, DcAAAD, DcSNAT, and DcASMT.…”
Section: F I G U R E 7 Effect Of Supplementary Melatonin Treatments Omentioning
confidence: 99%